UTILIZAÇÃO DE FUNGO DE BAMBU NA BIORREMEDIAÇÃO DE SOLO CONTAMINADO - Silva, Mayara Barbosa; Rondon, Josimara Nolasco (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611707757 Bioremediation is a technology for treating contaminated sites by the use of biological agents capable of modifying or decomposing pollutants. Whereas all plants can host one or more fungal endophytes, and these have great biotechnological potential the work aimed to study the feasibility of using endophytic fungi from Bambusa vulgaris (Poaceae) in the bioremediation of contaminated soils. For that were made soil contamination ex situ with diesel oil, chorume and the herbicide Roundup and fungus in the dilution of 5 x 105 conidios / mL were evaluated weekly the size of colonies and the fungal growth, the calculation of the initial and final volume of the pollutants tested by Tukey test at 5% probability. The endophytic fungus Fusarium moliniforme Sheld had 99% survival in the three contaminants evaluated within 30 days. The chorume had higher consumption and growth fungus. The samples that were contaminated with Roundup addition of nutrient solution obtained higher growth than that of the solution were added indicating the importance of nutrients for growth of biostimulation for some treatments. Larger quantities of the contaminants present better results in the treatment process of contaminated areas.